2018
DOI: 10.17265/2159-5542/2018.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Goal Attainments and the Role of Metacognitive Self in Task Accomplishment

Abstract: Based on metacognition theories we present a construct of metacognitive self (MCS) as self-awareness of biases. Contrary to counterintuitive idea metacognitive self fosters self-regulation in the area of goal's attainment. Study 1 (N = 118) showed that high metacognitive self individuals created more clear mental picture of their plans than low metacognitive self counter partners. Moreover participants high in metacognitive self undertook more actions to fulfill their goals then low MCS colleagues. Study 2 (N … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…MCS predisposition was an individual factor of growth during three years of studies. Moreover, the MCS predisposition promotes self-concentration and self-improvement, increases striving for a goal, helps to achieve reasonable goals, and supports the pursuit of autonomy (lower MCS involves working under supervision; Brycz et al, 2018a ). Longitudinal studies indicated that low MCS participants showed motivational deficits during three years of studies ( Kleka et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…MCS predisposition was an individual factor of growth during three years of studies. Moreover, the MCS predisposition promotes self-concentration and self-improvement, increases striving for a goal, helps to achieve reasonable goals, and supports the pursuit of autonomy (lower MCS involves working under supervision; Brycz et al, 2018a ). Longitudinal studies indicated that low MCS participants showed motivational deficits during three years of studies ( Kleka et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%